Pendidikan Karakter pada Anak Perspektif Washoya Al Abaa’ Lil Abnaa’ karya Syaikh Muhammad Syakir - Nor Mubin (Prodi Pendidikan Islam Anak Usia Dini Institut Agama Islam Daruttaqwa Gresik, 2020)
The position of character in Islamic education is seen as very important, because character is the practice of knowledge, character is also seen as an effective medium for receiving divine nurses and a means of seeking useful knowledge. Based on these problems, this research emerged. This research is based on library research, with descriptive analysis method. The concept of character education in children globally and the concept of character education in children in the perspective of Washoya Al Abaa 'Lil Abnaa'. Starting from the findings of this study, there are few suggestions that the education process is built on the basis of character and character education. kindness from a student and sincere love from an educator. The educational process can be conveyed in a good manner. There are 18 values ??of character education that come from religion, Pancasila, culture, and the goals of national education, namely: Religious, honest, tolerance, discipline, hard work, creative, independent, curiosity, national spirit, love for the country, respect for achievement, friendly or communicative, love peace, love to read, care about the environment, care about social, responsibility. In general, there are five character education methods that teach conceptual understanding, modeling, determining priorities, priority practice, reflection. While the character education method in the Washoya Al-Abaa book 'Lil Abnaa' can be concluded as a discussion method, memorization method, advice method (mau'izhah), habituation method, story method, exemplary method, dialogue method, targhib wa tahdib method, targhib method. wa tahdib.